Use of Dipeptidyl Peptidase 4 (DPP4) Inhibitors in Diabetic Nephropathy: A Prospective Cohort Study (Medical Forum Monthly, 2025)
Objective: To evaluate the glucose-lowering and reno protective properties of DPP-4 inhibitors in type 2 diabetes mellitus with nephropathy.Study Design: Prospective Cohort Study.Place and Duration of Study: This study was conducted at the Department of Medicine, Dr. Ruth KM Pfau Civil Hospital Karachi & Dow University Hospital, Ojha Campus from February 2022 to December 2023.Methods: This prospective cohort study used systematic sampling to enroll 300 adults with type 2 diabetes. Baseline and follow-up assessments at 12 and 24 weeks included blood glucose, BMI, UMA, ACR, lipid profile, and HbA1c. Following blinded administration of either Vildagliptin (50–200 mg) or Sitagliptin (25–100 mg), the results were examined using SPSS v25 and the relevant statistical tests.Results: Glycaemic and renal indices significantly improved in this 24-week study of 300 T2DM patients with renal dysfunction (Sitagliptin n = 164, Vildagliptin n = 136). FBS decreased from 154 to 135 mg/dl and the mean HbA1c decreased from 8.65% to 7.95% (p<0.05). Effectiveness with renal safety was demonstrated by the significant decreases in UMA and ACR, the stability of serum creatinine, and the slight decrease in BMI.Conclusion: DPP4 inhibitors can be used safely in type 2 DM with renal dysfunction to have fairly good glycemic control. In addition, we found it renal friendly, showing improvement in urine microalbuminuria and ACR and maintaining serum creatinine. So it can be used safely in type 2 DM patients with mild to moderate renal dysfunction who are reluctant to take insulin.